The Brazilian Executive Power and the abuses of freedom of expression regarding gender equality: anti-conduct and judicial control (Revista revoluciones, 2023)
This study aimed to analyze the effects and anti-conduct of the Brazilian executive in relation to the issue of gender and equity, from the perspective of freedom of expression. It is bibliographical research with a qualitative approach, where primary and secondary research sources were used. To delve into this dense universe, the work presented brief theoretical aspects of gender discourse as well as inverse and controversial behaviors of the Brazilian chief executive (2019-2022) and his ministries. In this perspective, the contextualization of women was unraveled from angles of history, taking as a premise the way in which gender violence permeates generations, in a cyclical repetition, and how populist governments have deconstructed the perspective of equity and rights of women, contrary to their duty to regulate and promote constitutional public policies with gender equity. Brazilian institutions, within their constitutional missions, use the regulatory power-duty, within the system of checks and balances, to denounce behaviors that violate Brazilian constitutional values. In this way, it is concluded that, thanks to the democratic regime and the judicial control of the acts of the powers, we can see the condemnation of a president of the republic, as a political agent and to the detriment of his lines that seek to deconstruct the political rights conquered. for the women. In addition to being didactic, the sentence is a thermometer showing that the institutions have matured over time and that the primacy of equality is not only material, but a premise of the Brazilian democratic State.
Keywords: judicial control; female; gender; freedom of expression; representation